Perancangan Sistem Informasi Aset Kendaraan di Kantor Dinas Syariat Islam Kota Banda Aceh - Rafiqah, Nurul; Idwan, Harry (Jurnal Ilmu Komputer dan Teknologi Informasi, 2025)
The Syariat Islam Office (DSI) of Banda Aceh plays a crucial role in supporting the strategic objectives of the Aceh Government in achieving its vision and mission. One of DSI’s primary tasks is to inventory the number of vehicle assets at the DSI office in Banda Aceh. The asset data is currently recorded manually in the form of archives and documents, and sometimes using Microsoft Excel. This process leads to inefficiencies in terms of space, security, time, and cost, making it difficult to retrieve the required vehicle asset data. Therefore, there is a need for the development of a Vehicle Asset Information System at the Syariat Islam Office. With this system, the vehicle asset data can be accessed anytime, anywhere, and from any computer. The system includes software requirements analysis, design, code generation, testing, and maintenance. This government vehicle asset management system is web-based, using MySQL as the storage medium and PHP as the programming language. The outcome of this system is the ability to process information related to vehicle assets, such as managing vehicle asset data comprehensively. Through this application, it is expected that staff will become more familiar with and utilize a more efficient information system.